Artérias dos Lobos Cervicais Tímicos em fetos de Sus scrofa Scrofa X Sus scrofa domesticus (Javaporco) - Eulálio, Francynny Helena Fonseca (2010)
The thymus is a lymphoid organ that starts its development at latter times of embrionary life and graows after birth until the puberty, when it begins to atrophy. It has the function to keep the animals immunoligal ability . The javaporco it s the result of the cross between a boar (Sus scroaf) and a domestic pig, which generates a fertile animal with 2n=37 chromosomes. The descriptive anatomy literature about the arterial patterns of javaporco is scarce. This way, new and wider studies are necessary. Thirty javaporco fetuses were used in the research (males and females), which were gotten in farms at Uberaba-MG countryside. The aim of this work was to study the arteries that are responsible for the upper vascularization of the thymus. A solution of Artecol 50% was injected in the fetuses , and they were fixed in a formol 10% solution, during 72 hours. The arteries emmited to the upper portion of the thymus were dissected and it was verified in both lobes , branches of subclavia, common carotid, cranial thyroid, caudal thyroid, cranial laryngeal, caudal laryngeal, superficial cervical, intern thoracic of the respective lobe. The left lobe was presented braquiocefalic trunk.